Influential factors in the application of the Lean Six Sigma and time-cost trade-off method in the construction of the ammunition warehouse - Albert Eddy Husin; Eko Arif Budianto (SINERGI, 2022)
Construction projects have developed so rapidly, one of which is the construction of warehouses. The warehouse discussed in this study is an ammunition warehouse. The construction of the ammunition warehouse has a deadline in accordance with the contract agreed between the owner, contractor and consultant. But in the implementation in the field, there was a delay in the work of the concrete structure. This study aims to obtain the dominant factors causing delays in the ammunition warehouse project by applying the Lean Six Sigma method and time-cost trade-off in solving the problem. Data processing used statistical analysis SPSS (Statistical Package for the Social Sciences), which was obtained from questionnaires filled out by experts. From this processing, the highest ten factors were obtained, namely 1. Inadequate planning and scheduling, 2. Implementation of work plans, 3. Delay in drawing up and approval of drawings, 4. Cost reduction, 5. Relationship between management and labor, 6. Relationship design internal team, 7. Lack of skilled manpower, 8. Flexibility, 9. Errors during construction and 10. Inaccurate prediction of craftsman production levels. This research is useful and beneficial for readers and can be developed again.